A calcination study on BeO ceramics for radiation dosimetry. (October 2020) - Altunal, V.; Guckan, V.; Ozdemir, A.; Yegingil, Z.
Graphical abstract: Highlights: The synthesis of BeO nano-particles using the co-precipitation and sol–gel methods. The role of calcination conditions on nanograins' phase formation, morphology, grain-growth behavior. The effect of calcination conditions on luminescence properties of BeO ceramic pellets. RL, TL and OSL characteristics of BeO ceramics. Decay components and lifetimes of OSL signals. Abstract: The aim of this study was to investigate the effect of calcination conditions on luminescence properties of BeO ceramics synthesized using co-precipitation and sol–gel methods. Structural and morphological characterizations were performed with X-ray Diffraction (XRD) and Scanning Electron Microscope (SEM) analyses. The role of calcination temperature and duration on micrograins' phase formation, morphology, grain-growth behavior, and luminescence characteristics were examined. Radioluminescence (RL), Thermoluminescence (TL) and Optically Stimulated Luminescence (OSL) techniques were used to characterize the luminescence signals. In the RL spectra of BeO ceramics synthesized with two methods, the characteristic emission peak between 200 and 500 nm, along with a wide emission peak between 700 and 800 nm due to anion defects were observed. To achieve a promising BeO dosimeter with highly sensitive TL and OSL signals for OSL dosimetry, the appropriate calcination conditions were determined for the co-precipitation and sol–gel methods as 900 and 1000 °C for 4 h, respectively.